TRANSFORMING ISLAMIC EDUCATION MANAGEMENT PARADIGMS: INTEGRATING VALUES AND TECHNOLOGY AMIDST GLOBAL DISRUPTION - Rizki Tamlikhul Fajri; Muhammad Khoirudin; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The rapid advancement of global disruption and digital technology presents a dual challenge for Islamic education institutions: preserving fundamental religious values while adapting to the demands of modern, efficient management. This study aims to analyze the transformation of Islamic education management paradigms from conventional bureaucratic models toward more adaptive, integrative, and humanist approaches. Employing a qualitative method with a library research approach, this study synthesizes recent scientific literature and empirical studies. Data analysis was conducted using content analysis to identify key strategic themes. The findings formulate three key paradigms: (1) Socio-cultural Adaptive Management, which emphasizes a cyclical mechanism of environmental scanning, value alignment, implementation, and evaluation; (2) Digital Islamic Management, which integrates data-driven decision-making with ethical foundations and spiritual leadership; and (3) The Humanist Paradigm, which reconstructs learning to focus on developing the students' natural potential and holistic character. The study concludes that the sustainability of Islamic education relies on a hybridization strategy that synergizes technological infrastructure sophistication with spiritual depth to produce competitive and integrous human resources.